2022
DOI: 10.3390/f13081164
|View full text |Cite
|
Sign up to set email alerts
|

Northern Provenances of Silver Fir Differ with Acclimation to Contrasting Light Regimes

Abstract: Phenotypic differentiation of Abies alba was identified among selected provenances originating from the northern edge of this species’ natural geographic range. We posited that although the seed sources of the study populations were not geographically distant, progenies would differ with respect to growth, needle pigment concentration, and values of photochemical parameters in response to contrasting light conditions. Potted seedlings of six provenances were grown for two seasons under low light (LL, 40% of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…Moreover, no significant differences were found between the fitted values for J max (and I sat ) and their corresponding observed values ( p< 0.05; Table 2 ). Our results are consistent with the findings of earlier studies ( Ye et al., 2013a , 2016 ; Robakowski et al., 2018 ; Yang et al., 2018 ; Ye et al., 2019 ; Zuo et al., 2019 ; Ye et al., 2020 ; Hu et al., 2021 ; He et al., 2022 ; Robakowski et al., 2022 ; Yang et al., 2023 ). In addition, previous results have also demonstrated that this model is suitable for fitting the J–I curves of algae and cyanobacteria ( Ye et al., 2013a ; Liang et al., 2018 ; Yang et al., 2023 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Moreover, no significant differences were found between the fitted values for J max (and I sat ) and their corresponding observed values ( p< 0.05; Table 2 ). Our results are consistent with the findings of earlier studies ( Ye et al., 2013a , 2016 ; Robakowski et al., 2018 ; Yang et al., 2018 ; Ye et al., 2019 ; Zuo et al., 2019 ; Ye et al., 2020 ; Hu et al., 2021 ; He et al., 2022 ; Robakowski et al., 2022 ; Yang et al., 2023 ). In addition, previous results have also demonstrated that this model is suitable for fitting the J–I curves of algae and cyanobacteria ( Ye et al., 2013a ; Liang et al., 2018 ; Yang et al., 2023 ).…”
Section: Discussionsupporting
confidence: 94%
“…The measurements of Chl a fluorescence were conducted using modulated and saturated light intensities set at 0.05 μmol photons m -2 s -1 and 15.3 mmol photons m -2 s -1 , respectively. Other parameters of the instrument were set following the method of Robakowski et al. (2022) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the rowan sprouts from roots when parent trees are cut (Rouvinen, Kouki 2011). Silver fir also performs well in open-area and non-stressed environments (Robakowski et al 2022) and it is a shade-tolerant species capable of sharing the environment with many tree species (Dobrowolska et al 2017). The shade-tolerant species are better survivors when mixed with others (Zeide 1985) and silver fir is also more resistant to drought (Vitali et al 2017).…”
Section: Discussionmentioning
confidence: 99%